2005
DOI: 10.1097/01.mao.0000172410.85992.21
|View full text |Cite
|
Sign up to set email alerts
|

Stapedotomy in Osteogenesis Imperfecta: A Prospective Study of 23 Consecutive Cases

Abstract: This study shows that safe and successful stapedotomy is possible in cases of stapes fixation in patients with osteogenesis imperfecta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 17 publications
3
26
1
7
Order By: Relevance
“…Our mean values for postoperative HG and ABG at short‐ and long‐term follow‐up are comparable with those reported in the previous series of stapes surgery in OI patients at the RUNMC (Table IV). Furthermore, the results of the extended Nijmegen series of patients with OI are comparable with the previous published results in the study by Vincent et al,31 and in the large Finnish,19 Dutch,32 Danish,5 and American17 studies, even though the methods used to calculate the average thresholds differ somewhat among the studies (Table IV).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our mean values for postoperative HG and ABG at short‐ and long‐term follow‐up are comparable with those reported in the previous series of stapes surgery in OI patients at the RUNMC (Table IV). Furthermore, the results of the extended Nijmegen series of patients with OI are comparable with the previous published results in the study by Vincent et al,31 and in the large Finnish,19 Dutch,32 Danish,5 and American17 studies, even though the methods used to calculate the average thresholds differ somewhat among the studies (Table IV).…”
Section: Discussionsupporting
confidence: 86%
“…They are summarized and their relative frequencies compared in Table III. Fixed footplates were present in all our operated ears, as well as in all cases from the series, in which stapes surgery was performed, as reported by others 5, 17, 20, 27–32. Fractured stapes crura and atrophic crura are often reported in hearing impaired OI patients with middle‐ear surgery, as well as thickened and brittle footplates.…”
Section: Discussionsupporting
confidence: 81%
“…44 Conductive hearing loss can occur through either disruption of the ossicular chain by fracture of the thinned ossicles or by obstruction of sound transmission by fixation of the stapes footplate. [45][46][47][48] Similar findings are present in reconstruction of fractured ossicles in OI, but comparative series are not available. [45][46][47][48] Similar findings are present in reconstruction of fractured ossicles in OI, but comparative series are not available.…”
Section: Ossicular Problemsmentioning
confidence: 74%
“…In former days, the diagnosis of OI has put off otologists to perform stapes surgery because of a higher risk of complications, such as bleeding of the mucosa, ossicular atrophy and the progressive character of the sensorineural hearing loss component inherent to the disease [Cremers and Garretsen, 1989], though, during the last few decades, reports on the results of stapes surgery in larger series of OI patients [Shea and Postma, 1982;Pedersen 1985;Cremers and Garretsen, 1989;Garretsen and Cremers, 1990;van der Rijt and Cremers, 2003;Kuurila et al, 2004;Vincent et al, 2005;Swinnen et al, 2009] have shown that a successful reduction in hearing thresholds may be expected in the majority of the OI patients with conductive hearing loss. Nevertheless, a few cases of total deafness following surgery have been reported [Garretsen and Cremers, 1990;van der Rijt and Cremers, 2003;Kuurila et al, 2004], as well as less beneficial results when revision surgery is concerned [Shea and Postma, 1982;Garretsen and Cremers, 1991b;van der Rijt and Cremers, 2003].…”
Section: Introductionmentioning
confidence: 99%